The immune response to intracerebral neural grafts. - Sloan, D; Wood, M; Charlton, H (1991)
Neural transplantation offers a potential therapeutic approach to a variety of neurological disorders, most notably those of a degenerative nature. However, the degree of immunological privilege (i.e. isolation from an immune response) in the brain, which is not absolute, may be a significant impediment to the survival of histoincompatible grafts. The nature of this privilege, together with the specific immune events leading to neural graft rejection, are discussed. As a consequence of this immune-mediated rejection, immunosuppression in some form might be necessary to guarantee long-term graft survival. Various strategies are being explored to suppress the immune response to neural grafts, not only for future use in clinical therapies, but also to bring intracerebral allo- and xenotransplantation to the attention of the general neurobiologist.